Evaluation of linearly-graded SiPMs for high resolution small-animal PET. (2nd December 2015) - Du, Junwei; Yang, Yongfeng; Berg, Eric; Bai, Xiaowei; Gola, Alberto; Ferri, Alessandro; Zorzi, Nicola; Piemonte, Claudio; Cherry, Simon R
Abstract: The performance of a position-sensitive silicon photomultiplier (PS-SiPM), a linearly graded silicon photomultiplier (LG-SiPM), was evaluated for use as a high resolution small-animal PET detector. This SiPM utilizes a combined resistive /capacitive current divider and a double quenching resistor in every SiPM microcell for position estimation. In this paper, using a 6 × 6 array of 0.45 × 0.45 × 6 mm 3 polished cerium-doped lutetium-yttrium oxyorthosilicate (LYSO) crystals, coupled to the center of the SiPM, we evaluated the detector performance, with a focus on applications in very high resolution small-animal PET. Measurements of signal-to-noise ratio, energy resolution and flood histogram quality were performed at different over-voltages (from ∼1.0 V to ∼7.5 V) and different temperatures (–6.5 °C, 0 °C, 10 °C and 20 °C) to find the optimal working conditions. The timing resolution was measured at an over-voltage of 3.0 V and at different temperatures. The results showed that all the crystals in the LYSO array could be clearly resolved, even at room temperature (20 °C). The best flood histogram quality was obtained at an over-voltage of ∼3.0 V and a temperature of –6.5 °C. Under these conditions, the average energy resolution, signal-to-noise ratio, and coincidence timing resolution were 22.3 ± 2.7%, 269.0 ± 24.2 and 828 ± 43 ps, respectively.